1999
DOI: 10.1111/j.1095-8649.1999.tb00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth dynamics of white and red muscle fibres in fast‐ and slow‐growing strains of rainbow trout

Abstract: Compared with fish of a slow-growing strain, fast-growing rainbow trout exhibited significantly smaller white fibre diameters, throughout development from hatching to 24 cm body length, although possessing similar total number of fibres. In contrast, in red muscle, no differences were observed in fibre diameter between the two strains, but the fast growing fish showed a significantly higher number of red fibres. The differences in growth rate between the two strains were related to the mean white fibre diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 44 publications
9
65
2
Order By: Relevance
“…From the kinetics of muscle growth in fish fed on D30 and D50 diets, it can be concluded that, for the body sizerange studied, the white muscle fibre hypertrophy increased linearly with the animal weight, which is in full agreement with a number of some other studies in fish (Weatherley et al 1988;Kiessling et al 1991;Valente et al 1999). In addition, although the fibre number was only linearly correlated with total body growth for D50 fish diet group, this further stressed the importance of the hyperplasia for growth in fish fed on diets having higher protein contents.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…From the kinetics of muscle growth in fish fed on D30 and D50 diets, it can be concluded that, for the body sizerange studied, the white muscle fibre hypertrophy increased linearly with the animal weight, which is in full agreement with a number of some other studies in fish (Weatherley et al 1988;Kiessling et al 1991;Valente et al 1999). In addition, although the fibre number was only linearly correlated with total body growth for D50 fish diet group, this further stressed the importance of the hyperplasia for growth in fish fed on diets having higher protein contents.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the higher percentage of smaller fibres (\2,000 lm 2 ) observed in the groups fed high-protein diets ([40%) suggest a greater potential for hypertrophic growth thereafter. Previous studies reported substantial differences in the relative contribution of both hypertrophy and hyperplasia of muscle fibres between rapid and slow growing strains of the same species (Weatherley et al 1979;Higgins and Thorpe 1990; Alami-Durante et al Valente et al 1999;Johnston et al 2000) in such a manner that rapid somatic growth is commonly associated to a higher rate of hyperplasia. These changes in fibre numbers were described in fish exhibiting different body sizes, and so, if size is taken into account these differences could be minimal (Kiessling et al 1991).…”
Section: Discussionmentioning
confidence: 97%
“…There are, however, other nonmutually exclusive explanations for these tradeoffs. For example, muscles and/or neuromuscular coordination may be less developed at a given size in fast-growing individuals (Weatherley and Gill 1987;Valente et al 1999). The increased weight or frictional drag of a stomach filled with food may also contribute to reduced locomotion (DeBenedictis et al 1978;Lind et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, after 10 weeks of refeeding the growth pattern changed, with increasing the frequencies of muscle fibers in the [ 50 lm diameter classes and decreasing the frequencies in the 10 and 30 diameter classes. This change in fiber distribution was demonstrated by the fish in all the fasted and fed groups and can be considered as evidence of hypertrophic muscle growth (Veggeti et al 1993;Valente et al 1999;Zimmerman and Lowery 1999;Johnston 2006).…”
Section: Discussionmentioning
confidence: 99%